Conversion of transpapillary drainage to endoscopic ultrasound-guided hepaticogastrostomy and gallbladder drainage in a case of malignant biliary obstruction with recurrent cholangitis and cholecystitis (with videos) - Nakai, Yousuke (Endosc Ultrasound, 2017)
Endoscopic ultrasound-guided biliary drainage (EUS-BD) has been increasingly reported as an alternative to percutaneous transhepatic biliary drainage in failed endoscopic retrograde cholangiopancreatography. Moreover, conversion to EUS-BD can be a good alternative when transpapillary biliary drainage is technically possible but complicated by cholangitis because EUS-BD enables one-step internal drainage not traversing the tumor. Herein, we report a case of recurrent cholangitis due to hemobilia and cholecystitis due to tumor involvement to the cystic duct after transpapillary stent placement, which was successfully managed by conversion to EUS-BD and EUS-guided gallbladder drainage in one session.